A Local Search Using Solution Fragments for the 2-Machine Bi-Criteria Scheduling Problem - HUANG, Gaofeng (Institutional Knowledge at Singapore Management University, 2007)
In this work, we introduce a local search strategy for combinatorial optimization problems which explores neighborhoods obtained using fragments of current solutions.We apply the approach to the well-knownNP-hard 2-machine bicriteria flowshop scheduling problem. Computational experiments using benchmark data show the approach to be effective when compared to other algorithms available for the problem.